Character Education through Local Content Curriculum of Budaya Alam Minangkabau - Mutiara Felicita Amsal; Zuwirna Zuwirna; Ahmad Johari Sihes (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
The study aims to determine whether Budaya Alam Minangkabau subject is able to shape the character of students in accordance with Minangkabau cultural values. The selection of learning strategies, the availability of teaching materials, and learning media determines the success of students' character planting. A Mixed Method was carried out where the population of this study was elementary school teachers in Padang. Budaya Alam Minangkabau is taught in grades 4, 5, and 6. The numbers of elementary school teachers are 939. For quantitative data, a sample of 100 teachers was determined, while for qualitative data the headmaster and school supervisor were assigned. Based on the results of research that has been done, the subjects of the Budaya Alam Minangkabau play a role in the formation of character, namely the planting of cultural values, ethics, morals and local wisdom. Thus, students have a high sensitivity to the cultural values of the region in order to remain sustainable and not uprooted from its own cultural roots. The formation of character in students is a value education, character education, and formal education, character education that aims to develop the ability of all school members to provide good and bad decisions, exemplary, maintain what is good and realize goodness in everyday life to the fullest heart. Through Budaya Alam Minangkabau subjects, students are expected to be able to recognize and become familiar with their own natural, social and cultural environment. Students have the stock, abilities and skills as well as knowledge about the area that is useful for themselves and the community in general, and develop noble values of local culture in order to support national development.